1975
DOI: 10.1161/01.res.36.4.490
|View full text |Cite
|
Sign up to set email alerts
|

Detection of latent function in acutely ischemic myocardium in the dog: comparison of pharmacologic inotropic stimulation and postextrasystolic potentiation.

Abstract: In poorly perfused myocardium with resultant ischemic dysfunction, augmentation of contractility can, under certain conditions, be used to detect viable but ordinarily noncontracting muscle. Two methods of inotropic augmentation, pharmacologic inotropic stimulation and postextrasystolic potentiation (PESP), were studied in acutely ischemic canine myocardium with controlled coronary blood flow. A caliper length gauge to record segmental shortening and left ventricular pressure was used to construct pressure-len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 25 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…A reduction in LVEF is attributed to decrease in amplitude of contraction or decrease in synchronicity. Asynchronies were shown in experimental animals in areas with a reduced coronary blood flow (Dyke et al 1975, Gillam et al 1984, Weyman et al 1984. Cardiac muscles with reduced coronary blood flow expand in early systole, because the ischemic muscles cannot support LV pressure during isovolumic contraction.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in LVEF is attributed to decrease in amplitude of contraction or decrease in synchronicity. Asynchronies were shown in experimental animals in areas with a reduced coronary blood flow (Dyke et al 1975, Gillam et al 1984, Weyman et al 1984. Cardiac muscles with reduced coronary blood flow expand in early systole, because the ischemic muscles cannot support LV pressure during isovolumic contraction.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that segmental systolic shortening is impaired promptly and markedly in ischemic zones of myocardium following coronary occlusion. Postextrasystolic potentiation of systolic shortening still may be elicited for a short time (Dyke et al, 1975;Crozatier et al, 1977;Boden et al, 1978) but, within 10 minutes, this is also abolished in the subendocardium (Crozatier et al, 1977). Studies using length gauges attached to the epicardium indicate that stable postextrasystolic potentiation may persist in this location for up to two hours (Boden et al, 1980), perhaps due to better perfusion known to exist in the epicardial myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Postextrasystolic potentiation restored wall motion in acute ischaemic areas. Other investigators found that under experimental conditions positive inotropic interventions increased wall force in acute ischaemic areas (Hood et al, 1969;Schelbert et al, 1971;Dyke et al 1975).…”
Section: Response To Postextrasystolic Potentiation During Pacing-indmentioning
confidence: 94%